Cannabidiol (CBD) product contamination: Quantitative analysis of Δ9-tetrahydrocannabinol (Δ9-THC) concentrations found in commercially available CBD products. (1st August 2022) - Johnson, Erin; Kilgore, Michael; Babalonis, Shanna
Abstract: Background: Regulation has not kept pace with the growth of the hemp-derived CBD market. We have evaluated the risk of Δ 9 -tetrahydrocannabinol (Δ 9 -THC) contamination in 80 unregulated products with comparison to a regulated control, Epidiolex®. Methods: Local and national brands of hemp-derived oil products were purchased online and from local retailers in central Kentucky (which carry both national and local brands). These were extracted by solvent extraction and quantified by liquid-chromatography tandem mass-spectrometry (LC-MS/MS) using a validated method. Results: Of the 80 unregulated products and Epidiolex®, Δ 9 -THC was detected above the limit of quantification (LOQ = 0.005 mg/mL) of the assay in 52 samples, ranging from 0.008 mg/mL to 2.071 mg/mL. Twenty-one of the products tested were labelled as "THC-Free", and 5 of these products contained detectable levels of Δ 9 -THC ranging from 0.015 mg/mL to 0.656 mg/mL. Conclusions: Consumers are taking hemp-derived CBD products without understanding the risks of unintentional consumption of Δ 9 -THC. This accidental use of Δ 9 -THC could have adverse effects on health and safety as well as potential legal consequences (e.g., child custody, impaired driving), as Δ 9 -THC drug test findings could impact employment, military, and sport eligibility status. Highlights: Hemp-derived CBD products commonly contain undisclosed Δ 9 -THC. Δ 9 -THC concentration ranged from 0.0008 to 2.071 mg/mL (mean = 0.620 mg/mL). Epidiolex® was used as an FDA-approved control; it contained 0.022 mg/mL Δ 9 -THC. Unintentional Δ 9 -THC consumption may lead to positive drug tests. Regulation of Δ 9 -THC content/CBD product labelling is essential for consumer safety.